Keterlibatan Orang Tua Siswa Miskin dalam Pembelajaran Pascapandemi - Luhjingga Panasari Urbaningrum; Nanang Martono; Elis Puspitasari (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2024)
This study aims to analyze the involvement of parents of economically disadvantaged students in post-pandemic learning, a crucial issue considering the demotivation experienced by many students after the COVID-19 pandemic ended. The research employs a descriptive qualitative method, utilizing interviews, observations, and documentation as data collection techniques. The informants include four parents, four students, and one teacher from SDN 2 Cidora, Lumbir Subdistrict, Banyumas Regency. Data were analyzed using thematic analysis to identify patterns of parental involvement. The findings reveal that parents of economically disadvantaged students engage in their children’s activities by providing physical facilities, offering motivation, paying attention to their children’s assignments, and supporting school activities. However, academic involvement remains low due to a limited understanding of the materials and time constraints. To overcome these challenges, parents rely on assistance from relatives as a form of social capital. The study concludes that economically disadvantaged students are able to compensate for the lack of economic capital through social and cultural capital, facilitating their adaptation to post-pandemic learning.